INTEGRATING THE ELECTRONIC CADAVER DISSECTION HOLOGRAPHY (ECDH) SYSTEM IN ANATOMY EDUCATION: PEDAGOGICAL IMPACT AND FORECAST - Boqijonova Nargizaxon Foziljon qizi (Modern American Journals, 2025)
Anatomy remains a cornerstone in the medical curriculum, yet traditional pedagogical approaches often fall short in delivering a clear, three-dimensional understanding of complex structures. This study investigates the educational impact of integrating the 3D Anatomy ECDH apparatus into anatomy instruction. Conducted at the Central Asian Medical University, the study employed a comparative model assessing traditional lecture-based teaching versus an augmented approach using 3D visualization. The findings indicate significant improvements in spatial awareness, test performance, and student engagement in the 3D-enhanced group. These results underline the growing necessity to blend technological innovations with conventional methods to enrich anatomical education and better prepare students for clinical realities.
Keywords: Anatomy education, ECDH apparatus, 3D visualization, medical students, teaching tools.